Analysis of the safety and efficacy of the self-pulling and latter transected technique in modified overlap anastomosis in total laparoscopic total gastrectomy - Wang, Jintian; Xiong, Jing; Wang, Pengcheng; Lin, Jianan; Zhong, Wenjin; Kang, Wengui; Wu, Chuying; Chen, Junxing; Zheng, Huida; Ye, Kai (Frontiers in Oncology, 2024)
Background Laparoscopic total gastrectomy plus lymph node dissection is an effective treatment method for patients with gastric cancer. With the development and popularization of laparoscopic techniques in recent years, surgeons have become more skilled in laparoscopic techniques. Totally laparoscopic total gastrectomy (TLTG) has been developed; however, digestive tract reconstruction remains difficult, especially with anastomosis of the esophagus and jejunum. Using the self-pulling and latter transection (SPLT) method combined with a linear stapler has effectively solved the problem of narrow space in esophagojejunostomy. Here, we examined the safety and effectiveness of the SPLT technique in TLTG compared with SPLT with traditional esophagojejunostomy overlap anastomosis.We retrospectively analyzed all patients with gastric cancer admitted to the